Chemistry Practicum Learning During the Covid-19 Pandemic: Determining the pH Scale of Acid-Base Natural Indicators with Semi-Quantitative Analysis Using Spectrum Color Measure Software - Siti Herlina Dewi; Sri Haryani; Triastuti Sulistyaningsih (International Conference on Science, Education, and Technology, 2021)
Learning in the laboratory or lab course is very crucial and inseparable in studying chemistry. Since the covid-19 pandemic, student's activities wet-laboratories were almost has eliminated. Several methods have been implementing to accomodating laboratory experiences, such as learning videos, virtual laboratories, and practicals using household/kitchen equipment (lab at home). This study aims to analyze the creative thinking skills of first-year chemistry students after implementing a do lab at home lab course. The learning activities embrace students to done, not only qualitative but also quantitative (semi-quantitative) analysis. The research was conducted in 2 classes of first-year chemistry students and focused on the aside-alkalimetry titration material. This study uses a mixed-method with explanatory sequential mixed methods design. The results of data analysis were showed an improvement in student's conceptual understanding, although it was not statistically significant. Even so, the level of student's creative thinking was increasing a lot. It founds that students could provide differents equipment and materials in the same problem, even beyond the goal learning expectation. Some students have high enthusiasm for the project design process. In addition, basic scientific skills, such as observing, formulating hypotheses, collecting data, and data analyze improved a lot too because they do a science lab.